Political Risk Aversion - Valderrama, Laura (Washington, D.C. : International Monetary Fund, 2009)
This paper studies the effect of individual uncertainty on collective decision-making to implement innovation. We show how individual uncertainty creates a bias for the status quo even under irreversible voting decisions, in contrast with Fernandez and Rodrik (1991). Blocking innovation is rooted in the aversion to the potential loss of political clout in future voting decisions. Thus, risk neutral individuals exhibit what we call political risk aversion. Yet individual uncertainty is not all bad news as it may open the door to institutional reform. We endogenize institutional reform and show a non-monotonic relationship between institutional efficiency and the size of innovation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet